Development of a Viral RdRp-Assisted Gene Silencing System and Its Application in the Identification of Host Factors of Plant (+)RNA Virus - Zhang, Wang; Qiu, Yanglin; Zhou, Lingyun; Yin, Jinlong; Wang, Liqun; Zhi, Haijian; Xu, Kai (Frontiers in Microbiology, 2021)
Gene silencing induced by hairpin RNA or virus infection expression is one of the major tools in genetics studies in plants. However, when dealing with essential genes, virus-induced gene silencing (VIGS) and transgenic expression of hairpin RNA could lead to plant death, while transiently expression of hairpin RNA in leaves is often less competent in downregulating target gene mRNA levels. Here, we developed a transient double-stranded RNA (dsRNA) expression system assisted by a modified viral RNA-dependent RNA polymerase (RdRp) in plant leaves. We show that this system is more effective in inducing gene silencing than the intron-spliced hairpin RNA expression. Furthermore, by using this system, we tested the role of the early secretory pathway during infection of Soybean mosaic potyvirus (SMV). We found that key components of the coat protein complex II vesicles are required for the multiplication of SMV. Overall, this dsRNA-based gene silencing system is effective in downregulating plant gene expression and can be used to identify host genes involved in plant-virus interactions.